Angiotensin II Receptor Type 1 1166 A/C and Angiotensin Converting Enzyme I/D gene polymorphisms in a Dutch sarcoidosis cohort - Kruit, A.; Ruven, H.J.T.; Grutters, et al., J.C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Background: The angiotensin II type 1 receptor (AT2R1) is the receptor for angiotensin II, a potent vasoconstrictor produced by ACE from angiotensin I. A recent study by Biller and colleagues revealed a gender-specific association between the AT2R1 1166 A/C gene polymorphism and disease susceptibility as well as a co-dependent association between AT2R1 1166 A/C and the angiotensin-converting enzyme (ACE) insertion/deletion polymorphism on ACE levels in a group of German sarcoidosis patients. Objective: The aim of our study was to compare our results from Dutch Caucasian sarcoidosis patients with the results of Biller et al. Design: Serum and DNA from 99 patients with sarcoidosis and from 327 healthy controls were included. The AT2R1 1166 A/C and ACE I/D polymorphisms and serum ACE levels were analyzed in all subjects. Results: No significant differences were found between the genotype distributions between the sarcoidosis patients and controls.The genotype distributions for either polymorphism between genders and between patients with progressive/chronic disease and those with acute/remission type disease were not different.The ACE D allele contributed significantly to higher ACE levels. This was true for both sarcoidosis patients and controls. There was no association between the AT2R1 1166 A/C genotype and ACE levels, nor did AT2R1 modify the ACE D/I effects on ACE levels. No significant differences were observed in co-incidence of ACE and AT2R1 genotypes between patients and controls. Conclusion: Our study could not confirm the findings by Biller and colleagues other than the influence of the ACE I/D polymorphism on serum ACE levels in both sarcoidosis patients and controls.